Impact of High-Dose Caffeine on the Preterm Ovine Cerebrum and Cerebellum - Atik, Anzari; De Matteo, Robert; Boomgardt, Meghan; Rees, Sandra; Harding, Richard; Cheong, Jeanie; Rana, Shreya; Crossley, Kelly; Tolcos, Mary (Frontiers in Physiology, 2019)
Caffeine is one of the few treatments available for infants with apnea of prematurity. As the recommended dosing regimen is not always sufficient to prevent apnea in some preterm infants, higher doses are prescribed. Little is currently known about the impact of high-dose caffeine on the developing brain; thus, our aim was to investigate the consequences of a high-dose regimen on the immature ovine brain. High-dose caffeine (25mg/kg caffeine base loading dose; 20mg/kg daily maintenance dose; n=9) or saline (n=8) was administered to pregnant sheep from 105 to 118 days of gestation (DG; term = 147 days); this is broadly equivalent to 28-33 weeks of human gestation. At 119DG, the cerebral cortex, striatum and cerebellum were assessed using immunohistochemistry. Compared with controls, caffeine-exposed fetuses showed (i) an increase in the density of Ctip2-positive layer V-VI projection neurons (p=0.02), Tbr1-positive layer V-VI projection neurons (p<0.0001), astrocytes (p=0.03) and oligodendrocytes (p=0.02) in the cerebral cortex, (ii) a decrease in the density of Cux1-positive layer II-IV projection neurons (p=0.01) in the cerebral cortex, and (iii) a reduction in the area of Purkinje cell bodies in the cerebellum (p=0.03). There was no difference (p>0.05) in: (i) the volume of the cerebral cortex or striatum, (ii) the density of neurons (total and output projection neurons) in the striatum, (iii) dendritic spine density of layer V pyramidal cells, (iv) the density of cortical GABAergic interneurons, microglia, mature oligodendrocytes or proliferating cells, (v) total cerebellar area or dimensions of cerebellar layers (vi) density of cerebellar white matter microglia, astrocytes, oligodendrocytes or myelin in high-dose caffeine-exposed fetuses compared with controls. Daily exposure of the developing brain to high-dose caffeine affects some aspects of neuronal and glial development in the cerebral cortex and cerebellum in the short-term; the long-term structural and functional consequences of these alterations need to be investigated.